2003
DOI: 10.1007/s00122-003-1264-6
|View full text |Cite
|
Sign up to set email alerts
|

Two critical factors are required for efficient transformation of multiple soybean cultivars: Agrobacterium strain and orientation of immature cotyledonary explant

Abstract: An efficient transformation system was developed for multiple soybean [Glycine max (L.) Merrill.] cultivars using Agrobacterium-mediated gene transfer. A significantly high number of hygromycin-resistant somatic embryos (SEs) was obtained when immature zygotic cotyledons were inoculated with Agrobacterium tumefaciens strain KYRT1 and when the abaxial side of explants was oriented upwards (i.e., the adaxial side of explants was in contact with the medium). Most hygromycinresistant SEs on selective medium were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…Even after more than two decades, the stable transformation of soybean cannot yet be considered as routine because it depends on the ability to bring together efficient transformation and regeneration techniques. Two methods have been successfuly used: particle bombardment Finer & McMullen, 1991;Christou & McCabe, 1992;Finer et al, 1992;Stewart et al, 1996;Aragão et al, 2000;Droste et al, 2002;Homrich et al, 2008;Wu et al, 2008;Li et al, 2009;Hernandez-Garcia et al, 2009;Xing et al, 2010;Viana et al, 2011) and Agrobacterium tumefaciens system Trick & Finer, 1998;Aragão et al, 2000;Yan et al, 2000;Ko et al, 2003Ko et al, , 2004Paz et al, 2006;Hong et al, 2007;Miklos et al, 2007;Liu et al, 2008;Wang & Xu, 2008;Wiebke-Strohm et al, 2011).…”
Section: Genetic Transformation Of Soybean Somatic Embryos Via Particmentioning
confidence: 99%
See 2 more Smart Citations
“…Even after more than two decades, the stable transformation of soybean cannot yet be considered as routine because it depends on the ability to bring together efficient transformation and regeneration techniques. Two methods have been successfuly used: particle bombardment Finer & McMullen, 1991;Christou & McCabe, 1992;Finer et al, 1992;Stewart et al, 1996;Aragão et al, 2000;Droste et al, 2002;Homrich et al, 2008;Wu et al, 2008;Li et al, 2009;Hernandez-Garcia et al, 2009;Xing et al, 2010;Viana et al, 2011) and Agrobacterium tumefaciens system Trick & Finer, 1998;Aragão et al, 2000;Yan et al, 2000;Ko et al, 2003Ko et al, , 2004Paz et al, 2006;Hong et al, 2007;Miklos et al, 2007;Liu et al, 2008;Wang & Xu, 2008;Wiebke-Strohm et al, 2011).…”
Section: Genetic Transformation Of Soybean Somatic Embryos Via Particmentioning
confidence: 99%
“…Studies with tumorigenic Agrobacterium strains (Pedersen et al, 1983;Droste et al, 1994;Mauro et al, 1995) and transient assays (Meurer et al, 1998;Droste et al, 2000) showed that soybean can be readily transformed by this bacterium. Currently, it is known that addition of acetosyringone during bacterial infection, combination of appropriate Agrobacterium strain and soybean cultivar, as well as development of super virulent bacterium strain and suitable plasmids increase efficiency of soybean transformation (Somers et al, 2003;Ko et al, 2003Ko et al, , 2004Wiebke-Strohm et al, 2011).…”
Section: Agrobacterium Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…High-frequency transformation relies on the highly efficient T-DNA delivery from Agrobacterium into plant cells (Ko et al 2003).…”
Section: Effects Of Major Factors On Tomato Transformationmentioning
confidence: 99%
“…However, longer sonication time may damage plant tissue (Santarem et al 1998). Way of placement of explant (adaxial side incontact with medium) on medium (Ko et al, 2003); exposure of soybean explants to AgNO 3 throughout shoot induction and shoot elongation (Olhoft et al, 2004); explant preparation in the presence of Agrobacterium culture and varying level of kanamycin during selection and regeneration (Zia et al, 2010b) are important for better recovery of transformants. Instead of kanamycin resistant plant, glufosinate resistant (bar gene) plants were produced by Zhang et al (1999) and Clemente et al (2000) using cotyledonary node explants of 5 days old seedlings.…”
Section: Soybean Agrobacterium Mediated Transformationmentioning
confidence: 99%